THE RELATIONSHIP BETWEEN NUMERICAL ABILITY AND THE ROLE OF PEERS AGAINST MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII OF SMP NEGERI 2 SANDEN - Aulia Khasanah; Widayati Widayati (Universitas Ahmad Dahlan, 2018)
Lack of numerical ability and inappropriate peer roles are thought to be some factors related to mathematics learning outcomes. Therefore, this study aims to determine whether or not a positive and significant relationship between the numerical ability and the role of peers to the results of learning mathematics eight grade class of SMP Negeri 2 Sanden Bantul regency in the academic year of 2016/2017. The population in this study are all students of eighth grade class of SMP Negeri 2 Sanden in the academic year of 2016/2017, which consists of 8 classes with a total of 217 students. Sample technique using random sampling technique and obtained eight grade class as a sample class. The technique of data retrieval is done by questionnaire method to know peer role, as well as a test method to know numerical ability and result of student learning of mathematics. Test of research instrument using validity test, reliability test, and different power test. The prerequisite analysis test includes a normality test, linearity test, and independence test—data analysis for hypothesis testing using product-moment correlation analysis and multiple linear regression analysis. The results showed that there is a positive and significant relationship of numerical ability and the role of peers to the results of teaching mathematics students of eighth grade class of SMP Negeri 2 Sanden Bantul regency in the academic year of 2016/2017. This is shown by Fcount = 4.051642194 ≥ Ftabel = 3.39. Coefficient of double correlation (R) = 0,4947604752 and linear regression equation Ŷ = 16,11822912 + 0,3822734012 X1 + 0,3787961883 X2. Relative contribution (RC) X1 = 58,7233% and (RC) X2 = 41,2767% and Effective Contribution(EC)X1 = 14,3748% and (EC)X2 = 10,1040%.